DEHYDROGENATIVE POLYMERIZATION OF NEW ALKYLSILANES CATALYZED BY CP(2)MCL(2)/RED-AL SYSTEM (M=TI, HF) - SYNTHESIS OF POLY(SUBSTITUTED 3-PHENYL-1-SILABUTANES) - WOO, HG; HAN, MK; CHO, EJ; JUNG, IN (KOREAN CHEMICAL SOC, 1995)
Substituted 3-phenyl-1-silabutanes such as 3-phenyl-1-silabutane (1), 3-(2,5-dimethylphenyl)-1-silabutane (2), 3-(p-chlorotolyl)-1-silabutane (3), and 3-naphthyl-1-silabutane (4) were prepared in 62-96% yield by reduction of the corresponding substituted 3-phenyl-1,1-dichloro-1-silabutanes with LiA1H(4). The dehydrogenative polymerization of the monomer silanes was carried out with Cp(2)MCl(2)/Red-Al (M=Ti Hf) catalyst system. The molecular weight of the polymers produced ranged from 700 to 1300 (vs polystyrene) with degree of polymerization (DP) of 5 through 16 and with polydispersity index (PDI)=1.1-2.1. The dehydrogenative polymerization of the monomer silanes with Cp(2)TiCl(2)/Red-Al catalyst system occurred at a faster rate and produced somewhat higher molecular weights of polysilane than that with Cp(2)HfCl(2)/Red-Al catalyst system.
Keywords: BOND METATHESIS MECHANISM; POLYSILANE HIGH POLYMERS; PRIMARY ORGANOSILANES; COMPLEXES; SILANES; DEHYDROPOLYMERIZATION; PHENYLSILANE; ZIRCONOCENE